A Review: Multiply and Accumulate Architectures for Digital signal Processing and digital image Processing (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The MAC (Multiply and Accumulate Unit) is the basic building block in the Digital signal processing and digital image processing systems. For efficient systems, the MAC unit should be fast with high precision and consuming low power. A MAC unit can be designed in Fixed-point arithmetic and Floating-point arithmetic. The use of Floating-point arithmetic gives high precision but it consumes more power and occupies more silicon area. To achieve high performance in a MAC unit, standard arithmetic can be implanted in its design. The IEEE-754 is floating-point arithmetic which can be used in the design of MAC. The use of the IEEE-754 standard improves the precision of the MAC unit. The conventional MAC units are designed by using HDL languages like the Verilog and the VHDL. By using these languages, the MAC unit can be designed in less time but designing the MAC unit at transistor level will increase the performance of the overall MAC unit. The cadence virtuoso can be used for designing the MAC at the transistor level. The design can be completed by using different technologies like 90nm gpdk or the tsmc 130nm etc. A floating-point MAC unit with half-precision using IEEE-754 in the transistor level will lead to better performance and high precision. Further we will discuss the different MAC architectures.